Enhancing The Security of E-Invoicing for Distribution Companies Through Image-Based PDF Conversion and QR Verification - Rochmatullah, Arief Noor; Wibowo, Ignatius Aris; Sarwosri, Sarwosri (Journal of Applied Informatics and Computing, 2025)
Distribution companies face significant challenges in securing electronic invoices, as PDF files are susceptible to unauthorized text extraction and manipulation. Prior solutions include SHA-256 digital signatures, and QR code-based verification. There are often require specialized tools, stable internet, or user intervention posing barriers for general trade customers with limited digital access. To address these limitations, this study proposes a hybrid e-invoicing method by converting invoices into image-based PDFs embedded with QR codes. This approach enhances document security, increases resistance to text manipulation, and ensures file sizes remain under 1 MB for smooth distribution via WhatsApp. A dataset of 1000 invoices was tested using OCR and FuzzyWuzzy string similarity to compare extractability between text-based and image-based formats. A composite score was calculated by combining file size and manipulation resistance metrics. Results show that image-based PDFs achieve a significantly higher score (0.595) compared to text-based PDFs (0.005), confirming their superiority in terms of size efficiency and data security. The findings demonstrate that this method provides a robust, low-cost, and scalable solution for secure invoice distribution in environments with limited infrastructure and technical literacy.